Hubungan Tinggi Badan menurut Umur dengan Kejadian Miopia pada Anak di SDN Cemara Dua Surakarta - Aprillia, Wahyu; Indrakila, Senyum; Primadewi, Novi (Nexus Kedokteran Klinik, 2014)
Background: Myopia is one of refractive errors most often occurs in children. Axial length appears to be a major determinant of refractive error. It has been theorized that a larger body might be associated with a greater axial length (AL) simply as a function of larger overall body size. Some studies suggest that taller people were more myopic than short people. This study aimed to analyze the relationship between height for age with myopia in children atÂ  SDN Cemara Dua Surakarta. Methods: An analytical observational study using a cross sectional design, was performed in Cemara Dua Surakarta Elementary School on May-June 2013. Total respondents were 180 people, taken by fixed disease sampling. Height for age was determined by respondents height z-score analysis that adjusted for TB/U growth chart based on WHO child growth standard. Status myopia obtained by screening using autorefractometer. Analysis of data was bivariate chi square, using SPSS program version 20.0 for windows. Results: This study shows 6 (3,3%) subject were stunted, 163 (90,6%) subject were normal, and 11 (6,1%) subject were heigt. Number of taller children in myopia were 7 people (63.6%) and not myopia were 4 people (36.4%). Chi Square test showed the results of p value = 0.351 (p < 0,05). Conclusions: There is no relationship between height for age with myopia in children at SDN Cemara Dua Surakarta. Keywords: Height, Age, Myopia.Â